Safe-Haven Korea? : Spillover Effects from UMPs - Ree, Jack (IMF Working Papers; Working Paper ;, 2014)
We examine how Korea's capital flows and trade have been affected by the quantitative easing (QE) of the United States and the quantitative and qualitative easing (QQME) of Japan. Korea is an intriguing case due to its borderline position between advanced and emerging market country groups, and the common perception that Korea competes fiercely with Japan in the world market for trade. We find that QE had little direct impact on capital flows to Korea, and tapering is unlikely to cause capital outflows from it owing to partial safe-haven behavior of capital flows to Korea. We also find that the exchange rate spillover from QQME to Korea has been limited both on trade and capital flow fronts.